BAD ATTACHMENTS: EMAIL AND QUEER ANTI-CENSORSHIP PROTESTS - McKinney, Cait (AoIR Selected Papers of Internet Research, 2020)
This paper examines a 1996 U.S. internet censorship protest that encouraged users to email a series of technically “indecent” files as attachments to Speaker of the House Newt Gingrich using an online email generator. These attachments were: a list of abortion clinics, a graphic illustration of condom-use instructions, and excerpted sexually explicit scenes from Gingrich’s own novel, 1945. Selecting from a drop-down menu, senders chose their attachments, completed a personalized message, and clicked send, all within a web-based form. By using the platform to inundate the Speaker’s email with attachments, senders cleverly broke the censorship provisions of the 1996 Communications Decency Act (CDA), putting themselves at risk to the criminalization of sexual expression online. The “bad attachments” protest grew out of the fact that online information about sexuality was vital to marginalized communities with limited access to other kinds of information channels—including queer and rural youth, and people living with HIV. This paper argues that the protest attachments constitute a queer, material digital practice, attuned to the political demand for ready information access as a means of survival.